Development of Self-Nano Emulsifying Drug Delivery System (SNEEDS) Containing Hibiscus sabdariffa L. extract, an Anticancer Against T47D Cells, as a co-chemotherapy of cisplatin - Efiana, Nuri Ari; Nurani, Laela Hayu; Wahyuningtyas, Nurma; Edityaningrum, Citra Ariani; Indratmoko, Septiana; Guntarti, Any; Ma’ruf, Muhammad (Journal of Food and Pharmaceutical Sciences, 2026)
Background: The first-line chemotherapy drug for breast cancer is cisplatin. However, it shows a high incidence of resistance. Therefore, Hibiscus Sabdariffa L (HS), containing strong anticancer compounds, was developed using a self-nano-emulsifying drug delivery system (SNEDDS), potentially as cisplatin co-chemotherapy. This study aimed to develop the HS SNEDDS providing anticancer activity against T47D breast cancer cells. Methods: Development of HS SNEDDS (F1-F7) with various surfactant and co-surfactant concentrations was carried out, followed by characterization of HS SNEDDS. The selected formulation was performed regarding the cytotoxicity on T47D cells and selectivity on Vero cells. Results: F7 as a selected formulation indicated a transmittance, globule size, PI, zeta potential, and emulsification time of 97.80%, 15.68 ± 0.19 nm, 0.12 ± 0.01, -8.05 ± 1.88 mV, and 24.76 ± 0.29 seconds, respectively. Furthermore, the IC50 of HS extract, HS SNEDDS, and Cisplatin on T47D cells were 0.37 ± 0.02, 0.24 ± 0.02, and 0.01 ± 0.001 mg/mL The selectivity index (SI) of HS SNEDDS and cisplatin were 108101.25 and 8351.84, respectively. Conclusion: HS SNEDDS providing the required characteristics could be obtained, and potentially be used as a co-chemotherapy of cisplatin, showing the cytotoxic effect on T47D breast cancer cells.